Absence of any effect of the electric charging state of particles below 10 nm on their penetration through a metal grid. Issue 2 (1st February 2018) - Alonso, Manuel
ABSTRACT: The effect of image force on the penetration of nanometer particles through metal grids remains a controversial issue. Experimental evidence of the existence and of the absence of such effect have both been reported in the past. A careful experimental work to measure penetration of particles in the mobility equivalent diameter range between 3.4 and 10 nm has been carried out. The possible particle size change between the aerosol generator and the filter has been considered, as well as the possible effect of particle number concentration on the filtration efficiency. The geometric dimensions of the filter allowed attainment of the fully developed parabolic flow velocity profile upstream the grid. Measurements were done at two values of the fiber Reynolds number, 0.09 and 0.12, much smaller than 1, as demanded by the currently accepted filtration theory. Penetration of charged particles, measured in three alternative ways, has been compared with penetration of uncharged and neutral particles (the latter consisting of a mixture of positive, negative, and uncharged particles). Two main conclusions have been reached: (1) the charging state of the particles does not affect their penetration through the metal grid and (2) the experimentally measured penetrations are fairly well predicted by the fan filter model of Cheng and Yeh. Copyright © 2018 American Association for Aerosol Research